Whey Protein Isolate Hydrogels Containing Cannabidiol Support the Proliferation of Pre-Osteoblasts - Daniel K. Baines; Varvara Platania; Nikoleta N. Tavernaraki; Karen Wright; Maria Chatzinikolaidou; Timothy E. L. Douglas (Gels)
Bone-associated pathologies are major contributors to chronic pathology statistics. Current gold standard treatments present limitations such as the ability to act as scaffolds whilst effectively delivering medications to promote cellular proliferation. Recent advancements in biomaterials have suggested whey protein isolate (WPI) hydrogel as a potential candidate to act as a scaffold with the capacity for drug delivery for bone regeneration. In this study, we investigate whey protein isolate hydrogels enhanced with the phytocannabinoid cannabidiol (CBD). The use of CBD in WPI hydrogels for bone regeneration is original. The results suggest that CBD was successfully incorporated into the hydrogels bound potentially through hydrophobic interactions formed between hydrophobic patches of the protein and the hydrophobic cannabinoid. The incorporation of CBD into the WPI hydrogels improved the mechanical strength of the hydrogels. The Young’s modulus was improved from 2700 kPa ± 117 kPa to 7100 kPa ± 97 kPa when compared to the WPI control, without plant-derived cannabinoids, to the WPI with the maximum CBD concentration. Furthermore, statistically significant differences for both Young’s modulus and compressive strength were observable between the WPI control and CBD hydrogel variables. The release of CBD from the WPI hydrogels was confirmed with the results suggesting a maximum release of 20 μM over the 5-day period. Furthermore, the hydrogels supported the proliferation and synthesis of collagen and calcium, as well as the alkaline phosphatase activity of MC3T3-E1 pre-osteoblasts, which demonstrates the potential of WPI/CBD hydrogels as a biomaterial for osseous tissue regeneration.